2018
DOI: 10.1371/journal.pone.0191299
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to obesogenic diet disrupts brain dopamine networks

Abstract: ObjectiveWe have previously demonstrated that insulin signaling, through the downstream signaling kinase Akt, is a potent modulator of dopamine transporter (DAT) activity, which fine-tunes dopamine (DA) signaling at the synapse. This suggests a mechanism by which impaired neuronal insulin receptor signaling, a hallmark of diet-induced obesity, may contribute to impaired DA transmission. We tested whether a short-term (two-week) obesogenic high-fat (HF) diet could reduce striatal Akt activity, a marker of centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…Similar results have been found in swine fed with an OD during the juvenile period; the gilts did not exhibit any signs of obesity, because they developed an adaptive response to the diet by reducing their food intake . By contrast, the feeding of rats with a high‐fat diet for 2 weeks around puberty induced significant adiposity and body weight gain . Similarly, in humans, an unbalanced dietary pattern during adolescence has been shown to cause greater adiposity and an increased metabolic risk …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results have been found in swine fed with an OD during the juvenile period; the gilts did not exhibit any signs of obesity, because they developed an adaptive response to the diet by reducing their food intake . By contrast, the feeding of rats with a high‐fat diet for 2 weeks around puberty induced significant adiposity and body weight gain . Similarly, in humans, an unbalanced dietary pattern during adolescence has been shown to cause greater adiposity and an increased metabolic risk …”
Section: Discussionsupporting
confidence: 76%
“…41 By contrast, the feeding of rats with a high-fat diet for 2 weeks around puberty induced significant adiposity and body weight gain. 42 Similarly, in humans, an unbalanced dietary pattern during adolescence has been shown to cause greater adiposity and an increased metabolic risk. 43 No differences were measured regarding the number of fetuses or fetal mortality in OD-fed females compared to CD group, suggesting that OD exposure during the peri-pubertal period did not affect reproductive performance, at least in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models allow for the investigation of more causal links between obesity and dopamine transmission and have begun to disentangle the effects of an obesogenic diet from adiposity. Short-term and chronic high fat diets (HFDs) as well as diet-induced obesity were shown to reduce D2R-mRNA and protein expression levels ( [96][97][98][99], but see [100]) ( Table 2). An elegant study suggests that diet-induced obesity may be the cause rather than the result of reduced D2R availability [18••].…”
Section: Obesity and Diet-related Dopamine Differencesmentioning
confidence: 99%
“…One study showed reduced D1R signalling when a diet high in saturated, but not monounsaturated fats (palm oil vs. olive oil), was administered [101]. Finally, diet-related changes in dopamine synthesis [108], release [59,102,105] and uptake (DAT) [98,99] have been observed.…”
Section: Obesity and Diet-related Dopamine Differencesmentioning
confidence: 99%
“…Further, obesity is associated with reward circuitry dysregulations, which is reflected in brain response to fat [ 30 , 52 , 53 ]. For instance, overweight compared to healthy-weight children showed greater BOLD responses in right insula, operculum, bilateral precuneus, and posterior cingulate cortex following milkshake consumption [ 9 ].…”
Section: Fat Tastementioning
confidence: 99%